Socio-Cultural Factors Influencing Farmers’ Adoption of Sustainable Agricultural Practices: A Systematic Literature Review (2020–2025) - Muthia Tri Fadhila; Edi Dwi Cahyono; Mas Ayu Ambayoen; Pipit Tunjungsari (Jambura Agribusiness Journal, 2026)
Adoption of sustainable agricultural practices (SAPs) remains uneven across regions, suggesting that existing approaches insufficiently account for the socio-cultural conditions shaping farmers’ decisions. While prior studies acknowledge social and cultural influences, they often examine these factors in isolation, limiting understanding of how they interact to enable or constrain adoption. This systematic literature review addresses this gap by synthesizing empirical evidence on the interconnected socio-cultural drivers of SAP adoption. Drawing on Scopus-indexed English-language journal articles published between 2020 and 2025, the review follows PRISMA 2020 guidelines. From 884 records, 87 empirical studies were included after screening. Using inductive thematic coding aligned with reflexive thematic analysis, five interrelated themes were identified: community social norms, cultural values and traditions, gender relations, knowledge and trust, and the institutional environment. The findings show that SAP adoption is not determined by single factors but by the interaction of social legitimacy, cultural alignment, trust-based knowledge exchange, and institutional responsiveness. Knowledge and trust emerge as key connecting factors linking other dimensions, mediating how norms, cultural meanings, and institutional support influence adoption. Conversely, adoption is constrained where entrenched norms reinforce existing practices, interventions conflict with local values, gendered inequalities limit access to resources and learning, and institutional arrangements fail to reflect farmers’ realities. The review highlights effective approaches, including peer-based social learning, participatory extension and co-design, trust-building processes, and institutionally supported interventions that are culturally resonant and gender-sensitive. These findings advance current understanding by reframing socio-cultural factors as interacting systems rather than discrete variables, with implications for designing more context-responsive and socially embedded agricultural interventions. Limitations include reliance on a single database, English-language publications, and the absence of formal quality appraisal.